Strategi Pengembangan Koleksi Perpustakaan Digital - Salmi Addin, Hanifatus; Anggraini, Hilda; Nur Riya Putri Yenti, Henel; Wandan Sari, Fuji; Hidayat, Irfan (Perpustakaan Universitas Gadjah Mada, 2024)
Developing digital library collections is essential in providing quality services to users. In this digital era, libraries must continue to consider the legal, ethical, and user needs implications associated with using digital resources. This research explores the basic theory of developing influential digital library collections to minimize possible obstacles. The research method used is a qualitative descriptive approach with a literature review. This research highlights that digital collection development requires ongoing efforts to ensure optimal relevance and availability of information for users. The research results show that various methods, such as direct procurement, collaboration, and digitalization, are used to increase the effectiveness of digital collection development in libraries. Librarians must consider appropriate collection development strategies to increase information accessibility and meet user needs in the digital era. Thus, the development of digital library collections plays an essential role in maintaining the relevance and quality of library services.